The Influence of Religiosity on Psychological Health In Medan City Taklim Majelis Women - Selamat Pasaribu; Nurussakinah Daulay; Rusydi Ananda (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
Women have an extensive role in fostering welfare in family and community life. Therefore, women need psychological well-being, characterized by a healthy, happy mental condition and the ability to face challenges or problems by utilizing all their potential. A person with psychological well-being is also characterized by self-acceptance, personal growth, positive relationships with others, autonomy, environmental mastery, and having a purpose in life—religiosity is a factor that influences psychological well-being. Religiosity requires a person to seek harmony, understanding, belief constantly, a strong belief in divine teachings, carry out religious practices or rituals well, and have moral and ethical values. This research aims to determine the extent of the influence of religiosity on the psychological well-being of Taklim assembly mothers. This research uses a quantitative approach. The research population is all assemblies in Medan City, which has 21 sub-districts. The sample uses a cluster area random sampling technique. Sampling is done using a random area sampling technique based on the selected region or sub-district. These findings indicate that religiosity influences the psychological well-being of Taklim assembly women in Medan City. This is obtained from the calculated coefficient value of 9.292 and a sig value <0.05. So, it can be said that religiosity directly influences psychological well-being empirically. So, it is believed empirically that religiosity positively and significantly influences psychological well-being, in other words, variation. The level of welfare (psychological well-being) at the Medan City Taklim Council is influenced by religiosity.